Faktor Kepuasan Kerja Terhadap Kinerja Islam Pada Karyawan Muslim Tenaga Kependidikan di Fakultas Ekonomi dan Bisnis Universitas Airlangga - Pradhana, Angga Bayu; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of this study was to determine the effect of job satisfaction factors on Islamic performance against Muslims employee of Workforce Education in Faculty of Economics and Business Airlangga University.This study used a questionnaire in the primary data collection and quantitative approach to the multiple regression analysis method. Criteria in this study population is Muslim employee education personnel status as a civil servant at the Faculty of Economics  and Business Airlangga University totaling 87 people, consisting of 85 Muslim employees and 2 non-Muslim employees. While the sample in this study amounted to 85 Muslim employees. Sampling using sampling saturated technique, because the population in this study is less than 100 people.The results showed that the factors work itself, salary or wages, and co-workers has a positive effect (unidirectional) and partially significant to the Islamic performance. While factors promotional opportunities and working conditions negatively (opposite) and partially not significant to the Islamic performance, and supervision factors and partially significant positive effect on the Islamic performance. While simultaneously, 6 exogenous variables have a significant effect on the Islamic performance Muslim employees of educational staff in the Faculty of Economics and Business Airlangga University.